SIMULASI LUAS PENAMPANG STREET INLET JALAN YOS SUDARSO KOTA PALANGKA RAYA - Kamiana, I Made (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2021)
Abstract: The inaccurate of cross-sectional area of the street inlet can be one of the flooding causes on the road surface when the rainfall intensity is very high. This study aims to simulate the relationship between the cross-sectional area of the street inlet and the street inlet distance at Jalan Yos Sudarso, Palangka Raya City. The length of the reviewed road is 0.5 km. The simulation using an analytical approach. In the simulation, the street inlet distance variations are 5 m, 10 m, and 20 m; variations of the design discharge return period are 2 years, 5 years, and 10 years; variations of design water depth in the gutter are 1 cm, 1.5 cm, and 2 cm. The results show, the cross-sectional area of street inlet is getting bigger if the street inlet distance is getting bigger. At each street inlet distance, the cross-sectional area of street inlet is directly proportional to the design discharge and inversely proportional to the design water depth in the gutter. The cross-sectional area of street inlet at the street inlet distance of 5 m ranges from 62.72 to 284.42 m2, at the street inlet distance of 10 m ranges from 177.84 to 498.29 m2, and at the street inlet distance of 10 m ranges from 345.41 to 809.62 m2.Keywords : street inlet, cross-sectional area, street inlet distance, design discharge, gutterAbstrak: Tidak tepatnya luas penampang street inlet dapat menjadi salah satu penyebab genangan di permukaan jalan ketika hujan lebat. Penelitian ini bertujuan untuk mensimulasikan hubungan luas penampang street inlet dengan jarak street inlet. Jalan yang ditinjau adalah Jalan Yos Sudarso Kota Palangka Raya. Panjang jalan yang ditinjau 0,5 km. Simulasi dilakukan secara analitis. Dalam simulasi tersebut, variasi jarak street inlet yaitu 5 m, 10 m, dan 20 m; variasi periode ulang debit rencana yaitu 2 tahun, 5 tahun, dan 10 tahun; variasi kedalaman air rencana di saluran pembawa yaitu: 1 cm, 1,5 cm, dan 2 cm. Dari hasil simulasi diketahui luas penampang street inlet semakin besar apabila jarak street inlet semakin besar. Pada setiap jarak street inlet, luas penampang street inlet berbanding lurus dengan debit rencana dan berbanding terbalik dengan kedalaman air rencana di saluran pembawa. Luas penampang street inlet pada jarak street inlet 5 m berkisar antara 62,72-284,42 m2, pada jarak street inlet 10 m berkisar antara 177,84-498,29 m2, dan pada jarak street inlet 20 m berkisar antara 345,41-809,62 m2.Kata kunci : luas penampang street inlet, jarak steet inlet, debit rencana, saluran pembawa